Patterns of politicization following triggering events: the indirect effect of issue-owning challengers - Van der Brug, Wouter; Berkhout, Joost (Frontiers in Political Science, 2024)
Changes in party systems do not always occur gradually. While structural changes in societies lead to new tensions and potential conflicts, these conflicts often become politicized in the wake of ‘triggering events’. However, such events do not always lead to the politicization of an issue. This study addresses the question why potentially triggering events sometimes produce extensive political attention and conflict around an associated issue, whereas in other circumstances very similar events do not generate much political attention or contestation. Some scholars highlight the strategic incentives of party political elites (the top-down perspective) whereas others focus on the key role of political challengers in politicizing issues (‘the bottom-up perspective)’. We focus on three events that potentially trigger the politicization of immigration (9–11, Banlieus riots and the Cartoon crisis) and identify anti-immigration parties as challengers of government parties. Based on political claims analysis of newspapers in seven European countries, we find that government parties exert strong control over the political agenda, both in terms of salience as in positional terms. However, when anti-immigration parties are large and in opposition, they do play an important role in politicizing the issue of immigration. Since anti-immigration parties have increased their vote share over the past decade and typically remain in the opposition nevertheless, it is likely that future events will lead to further politicization of the issue of immigration.